Mathematical Reasoning Ability Based on Interactive Multimedia on Learning Outcomes of Geometry Transformation Material - Franky Alfrits Oroh; Majid Majid; Abdul Djabar Mohidin (STAI Hubbulwathan Duri, 2023)
The advancement of the world and the rapid development of IT have had a good influence on world civilization. Guaranteed quality learning is how the teacher can utilise multimedia learning. This study aims to describe student learning results in mathematics subject matter geometry transformation based on interactive multimedia. This qualitative descriptive research was conducted at a state junior high school in Suwawa 2022-2023 with a total of 27 students. Observation techniques are used to collect research data about student tests and interviews in the learning process through interactive multimedia learning. The indicators are the results of student observations in receiving learning that reaches the whole, the results of teacher observations in managing learning reach the whole, and the assessment of mathematics learning outcomes interviews that reach a minimum of 80% or overall students who achieve the minimum completeness criteria or (KKM = 75). The average learning outcomes in stage I have shown an increase, with 11 students achieving a completion rate of 63.24%. In stage II, this figure rose to 24 students, representing a completion rate of 83.87%. This tool has the potential to be advantageous for educators in the creation of multimedia-driven instructional materials, hence fostering increased student engagement and participation. The impact of technological advancements in the field of education is characterised by a notable augmentation in invention. This surge in innovation has the potential to cultivate a generation that possesses enhanced skills and preparedness to effectively address the evolving demands of the future. In addition to assessing educational achievements, it is imperative to take into account students' perspectives on the utilisation of interactive multimedia in the process of learning.